Phenotypes, endotypes and genotypes of atopic dermatitis and allergy in populations of African ancestry on the continent and diaspora - Lunjani, N.; Kerbelker, T.; Mdletshe, F. B.; Hlela, C.; O’Mahony, L. (Frontiers in Allergy, 2024)
Atopic dermatitis is a complex inflammatory condition characterized by synergist interactions between epidermal and immune related genotypes, skin barrier defects and immune dysregulation as well as microbial dysbiosis. Ethnicity-specific variations in clinical presentation, immune endotypes and genetic susceptibility have been described in diverse populations. We summarize available data with specific consideration of AD in populations of African ancestry. Some highlights include the observation of AD lesions on extensor surfaces, lichen planus-like AD, prurigo type AD and follicular AD in African populations. In addition, a consistent absence of dominant filaggrin gene defects has been reported. The detection of normal filaggrin protein content in AD skin implicates the contribution of alternative mechanisms in the pathogenesis of AD in African patients. Markedly high IgE has been described in paediatric and adult African AD. While Th2, Th22 and Th17 activation in African AD skin shares the same direction as with other populations, it has been noted that the magnitude of activation is dissimilar. Reduced Th17 cytokines have been observed in the circulation of moderate to severe paediatric AD.